Yes we can? Effects of a participatory visioning process on perceived climate efficacy - Peisker, Jonas; Schinko, Thomas (Frontiers in Climate, 2023)
Lack of perceived efficacy can be an important barrier to climate mitigation action at various scales. Here, we study how a participatory visioning process, the Climate Modernity workshop in Styria, Austria, affected participants’ efficacy outcomes. To this end, we conducted two survey waves to elicit self- and response efficacy regarding possible mitigation measures. We estimate difference-in-differences models and corroborate the findings using qualitative participant feedback. The results indicate that the intervention tends to decrease personal self-efficacy, in particular with regard to controversial topics like the transformation of the transport system. This suggests that participatory stakeholder processes can draw attention to the conflict potential and complexity of specific mitigation policies, decreasing the perceived feasibility of implementing them. The workshop, however, tended to increase particpants’ personal response efficacy, particularly regarding voting for pro-environmental candidates. Accordingly, participatory processes could raise trust in the democratic process and in the effectiveness of making a green voting decision.